2021
DOI: 10.31729/jnma.5742
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Simultaneous Total Knee Arthroplasty in Elderly Patients with Severe Osteoarthritis of Knee Joint in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Total knee arthroplasty is one of the most successful orthopedic surgeries performed in recent decades. However, there are controversies regarding the simultaneous or staged bilateral total knee arthroplasty. The aim of this study is to find the prevalence of bilateral total knee arthroplasty in elderly patients among severe osteoarthritis of knee joints in a tertiary care hospital. Methods: This is a descriptive cross-sectional study conducted from hospital records of 2015 to 2019 in elderly pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We had very few total joint replacement candidates compared to the developed world that might be because of lack of awareness, increased cost of implants, and no insurance policy. 15 Most of our patients with TKR were simultaneous bilateral replacements which we found to be safe, effective with early functional recovery, higher patient satisfaction, and cost-effective in properly selected candidates similar to K.C KM et al 16 On geographical variation, most of our patients were local from Chitwan followed by nearby districts Nawalparasi, Makwanpur and some of them were far from Chitwan like Syanja, Rukum and Kathmandu.…”
Section: Discussionmentioning
confidence: 59%
“…We had very few total joint replacement candidates compared to the developed world that might be because of lack of awareness, increased cost of implants, and no insurance policy. 15 Most of our patients with TKR were simultaneous bilateral replacements which we found to be safe, effective with early functional recovery, higher patient satisfaction, and cost-effective in properly selected candidates similar to K.C KM et al 16 On geographical variation, most of our patients were local from Chitwan followed by nearby districts Nawalparasi, Makwanpur and some of them were far from Chitwan like Syanja, Rukum and Kathmandu.…”
Section: Discussionmentioning
confidence: 59%
“…Studies have reported substantial improvements in ROM following TKA for FFD using stepwise algorithms for correction. 9,34,35 Correcting fixed deformities in TKA has been shown to provide effective pain relief and functional improvement. 35 Quah et al observed a significant reduction in pain scores postoperatively, with many patients experiencing pain relief and improved functional outcomes.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…9,34,35 Correcting fixed deformities in TKA has been shown to provide effective pain relief and functional improvement. 35 Quah et al observed a significant reduction in pain scores postoperatively, with many patients experiencing pain relief and improved functional outcomes. Several studies have reported on patient satisfaction following surgical correction.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations